Dialecticisms in novel of Mariya Matios “Sweet Darusya” (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The article deals with dialecticisms in novel of Mariya Matios “Sweet Darusya”, their phonetical, lexical, phraseological and grammatical types are analyzed. The attempt of systematization of dialect vocabulary and phraseology with taking into consideration their structural, semantic, functional-stylistic and genetic peculiarities are made.
Keywords: dialecticism; dialect vocabulary; dialect phraseology; dialect peculiarities